Travel Fund (Review of Economic Studies, 2001)
Journal Article Travel Fund Get access The Review of Economic Studies, Volume 68, Issue 4, October 2001, Page 905, https://doi.org/10.1111/1467-937X.00195 Published: 01 October 2001